Click grafting of alkyne-containing vinyl polymers onto biosynthesized extracellular matrix protein containing azide functionality and adhesion control of human umbilical vein endothelial cells1. Issue 52 (10th June 2015) - Yamada, Tomoki; Takasu, Akinori
<x xml:space="preserve">Abstract</x> Biosynthesized aECM-CS5-ELF containing p-N3Phe was coupled with alkyne-containing vinyl polymers via click reaction. Specific adhesion of human umbilical vein endothelial cells onto the composite surface and subsequent temperature-sensitive detachment were also demonstrated.